Apatinib combined with temozolomide treatment for pseudoprogression in glioblastoma: A case report. Issue 49 (9th December 2022) - Zhao, Mingming; Ma, Haodong; Cheng, Peng; Yang, Hongjie; Zhao, Yang; Han, Qian
Abstract : Rationale: Glioblastoma is the most common malignant tumor of the central nervous system, which originates from glial cells and corresponding precursors. Due to its strong invasion and rapid growth, the prognosis of patients after treatment is very poor and easy to relapse. Patient concerns: In August 2015, a 48 years old man with a relapse of glioblastoma. Diagnoses: The patient was diagnosed by computed tomography, magnetic resonance imaging, and pathological biopsy in this case report. Interventions: The patient underwent 2 surgeries, radiotherapy, and multiple regular chemotherapy sessions over the next 6 years. Apatinib, an inhibitor of vascular endothelial growth factor receptor 2 was given to treat recurrent glioma. Outcomes: It was found that radiotherapy combined with temozolomide administration often increased the size of the original lesion or produced a new glioblastoma lesion. The lesion development was similar to tumor progression, which was called pseudoprogression. And it significantly prolonged the survival of this patient. Lessons: Surgery, radiotherapy and chemotherapy with apatinib and temozolomide are effective to treat the patients with pseudoprogression in glioblastoma.